Immunomodulation of nutritional formula containing epigallocatechin-3-gallate, ginseng extract, and polydextrose on inflammation and macrophage polarization - Wang, Yi; Hu, Yaozhong; Niu, Zhenhua; Zhang, Xuejiao; Fan, Dancai; Ji, Xuemeng; Lv, Huan; Wang, Shuo; Zhao, Yanrong (Frontiers in Nutrition, 2024)
Single nutrient likes polyphenol or dietary fiber have been exhaustively investigated to validate their positive intervention in health or disease. Meanwhile, the common interaction of inner systems with the nutrient complex has not been well elucidated, which raises the scientific issue of the modulatory effect of the nutrient complex on immunity. The representative prebiotics of epigallocatechin-3-gallate (EGCG), ginseng extract, and polydextrose (PDX) were selected on behalf of the classification of polyphenol, flavone or polysaccharides, and dietary fiber to generally cover the daily food intake in this study to explore their intervention in inflammation and macrophage polarization. The intervention of selected nutrients on inflammation and macrophage polarization has been evaluated against macrophages to unveil their comprehensive effects. The synergistic effect of selected nutrients was demonstrated by inhibiting M1 macrophage polarization and the promotion of M2 macrophage polarization. Then, the nutrient formula was set up to verify the intervention effect, and the results revealed the significant inhibition of cell inflammation and the effect on cell proliferation through promoting the cell cycle in the G2 phase. The nutrient complex could inhibit M1 macrophage polarization to inhibit M1-mediated inflammation and promote M2 macrophages for anti-inflammatory effect and enhance cell phagocytosis. Moreover, the varied intervention effects of the nutrient complex with different formulas could be summarized. In general, the formula containing EGCG, ginseng extract, and PDX was demonstrated to possess an enhanced immunomodulatory effect on cell inflammation and macrophage polarization, which could potentially inspire the investigation of complex nutrients in health and diseases.